FAUNA MOLUSKA PERAIRAN DERAS DI DUA SUNGAI DAERAH RIAU DARATAN - M. DJAJASASMITA (Research Center for Biology-Indonesian Institute of Sciences, 1985)
M. DJAJASASMITA. 1985. Molluscan fauna of the two stream rivers of Riau. Berita Biologi 3(3): 121 - 124. - A preliminary study on the composition and population density of the molluscan fauna in the streams of the rivers Tiwi (stony and sandy bottom) and Tandun Kecil (clayed muddy bottom), in Riau, East Sumatra, has been carried out, in July 1977. The molluscs collected consisted of Brotia costula, Clea bocki and Corbicula moltkiana in Tiwi River and B. costula, Pseudodon vondembuschianus and Rectiden graeilis in Tandun Kecil River. B. costula dominate in both localities, 86.08% and 72.58% respectively; the other species range from 2.42% to 25%. In general both localities have low molluscan population density, 41.2 m